A comprehensive framework for Internet of Things development: A grounded theory study of requirements. Issue 1 (13th November 2019) - Ghaffari, Kimia; Lagzian, Mohammad; Kazemi, Mostafa; Malekzadeh, Gholamreza
Abstract : Purpose: Despite the availability of prior studies on the Internet of Things (IoT) development, they have largely focused on challenges associated with evolving IoT. Hence, identifying requirements for IoT development, as a multifaceted phenomenon, whereby the challenges would be tackled remains a less-explored valuable line of inquiry. The purpose of this paper is to present a holistic view of crucial building blocks of IoT development, in order to fill this gap. Design/methodology/approach: This paper conducts empirical research using a grounded theory (GT), centering on semi-structured interviews with 25 experts involved in the Iranian IoT development effort. Data were analyzed by using MAXQDA software. Findings: This study presents a conceptual framework of requirements for IoT development, consisting of 14 concepts and 5 categories. The findings reveal that strategic, interactive, institutional, market-oriented and information and communication technology (ICT) infrastructure requirements play a salient role in facilitating IoT development. Practical implications: The findings of this study shed some light on the momentous aspects of IoT development. Practitioners including governmental policymakers, industry and private sectors could benefit from the policy recommendations offered in this study in terms of strategic viewpoint, legal issues, business perspective and technological readiness. Originality/value: From the methodological aspect, the present research is among the first studies on utilizing GT for exploration of requirements for IoT development. From the theoretical perspective, a remarkable achievement of this study is to profoundly discover some less-explored concepts of IoT development such as commercialization, feasibility study, futurology and institutional aspects. Furthermore, findings of this study highlight the contribution of innovation systems theory for the IoT development area in terms of alignment of the emerged requirements for IoT development with the functions of this theory.